A Pedagogical Framework for Developing Elementary School Students’ Spatial Thinking Through Geometric Transformations - Zahra Nur Aprilia, Annisa; Sabila; Sari, Arilda Fitria; Nufus, Rizka Kamilatun; Reza, Sandryna Fathia; Faujiah, Evi; Dwiprabowo, Risky (Delta: Jurnal Ilmiah Pendidikan Matematika, 2025)
Spatial thinking is a fundamental cognitive ability that plays a crucial role in understanding and reasoning about geometric concepts, particularly geometric transformations. This study aimed to examine the effectiveness of a pedagogical framework designed to develop elementary school students’ spatial thinking through geometry transformation learning. A quasi-experimental method with a one-group pretest–posttest design was employed involving 28 upper-grade elementary school students. The pedagogical framework integrated contextual problems, visual and concrete exploration, guided spatial reasoning, representational transformation, and reflection within learning activities on translation, reflection, rotation, and dilation. Students’ spatial thinking abilities were assessed across four aspects: spatial visualization, mental rotation, spatial orientation, and geometric transformation reasoning. Data were analyzed using descriptive statistics and a paired-samples t-test. The results indicated a significant improvement in students’ spatial thinking abilities, with a notable increase in mean posttest scores compared to pretest scores. The paired-samples t-test revealed a statistically significant difference (p < 0.001), accompanied by a very large effect size (Cohen’s d = −34.6), indicating strong practical effectiveness. These findings demonstrate that the proposed pedagogical framework is highly effective in enhancing elementary school students’ spatial thinking and offers a meaningful instructional approach for geometry learning at the primary education level.